Gry i zabawy ruchowe na lekcjach wychowania fizycznego w edukacji wczesnoszkolnej z uwzględnieniem sytuacji trudnych – kilka przykładów z praktyki - Wojewoda , Anna (Studia Edukacyjne, 2023)
Physical education lessons in grades 1-3 of primary school play an important role in the processes of upbringing and socialization. Due to the great need to move and relieve tension at this age, they are a kind of safety valve. During physical education classes, students interact with one another more often. During contact team games or games focused on competition, tensions often occur, personal space is violated, and the child’s emotions take over. This article presents three movement games: a bricklayer, a wolf and seven kids, and piggy in the middle. Authentic difficult situations (such as aggression, escaping from the classroom, throwing objects) that occurred during physical education lessons are described here, and proven solutions based on the teacher’s own experience are presented. The examples provided are not a ready-made recipe for every difficult behavior, but they show how small steps can be calmed down or worked out with the appropriate cooperation of the student, peers, parents, specialists, and the teacher.